Layer V Neocortical neurons from individuals With drug-resistant epilepsy show multiple synaptic alterations but lack somatic hyperexcitability - Luis A. Márquez; Christopher Martínez-Aguirre; Estefanía Gutierrez-Castañeda; Ernesto Griego; Isabel Sollozo-Dupont; Félix López-Preza; Mario Alonso-Vanegas; Luisa Rocha Arrieta; Emilio J. Galván (PLoS ONE, 2026)
Although neuronal hyperexcitability is the primary mechanism underlying seizure activity in epilepsy, little is known about how different neuronal mechanisms at different organizational levels contribute to network hyperexcitability in the human epileptic brain. In this study, we determined a series of cellular and synaptic properties of Layer V pyramidal neurons from neocortical tissue of patients with drug-resistant epilepsy that may contribute to the hyperexcitable state associated with epilepsy. Using the whole cell, patch-clamp technique, and extracellular recordings, we determined the passive and active electrophysiological properties of Layer V pyramidal neurons with regular spiking phenotypes from temporal, parietal, and frontal neocortices surgically resected from individuals with drug-resistant epilepsy. Also, the glutamatergic strength, the synaptic coupling between presynaptic volleys and field excitatory postsynaptic potentials, and short-term, frequency-dependent plasticity were determined. Our data revealed that pyramidal neurons exhibit minimal spontaneous synaptic activity, similar resting membrane potentials, and input resistance values among the temporal, parietal, and frontal neocortices. Although frontal neurons were more hyperexcitable than temporal and parietal neurons, the firing output was comparable to that previously observed in non-pathological human tissue. In contrast, the extracellular recordings uncovered significant decoupling between presynaptic excitability and postsynaptic activity and the lack of short-term depression in response to gamma-range (30 Hz) repetitive stimulation. Our data suggest that neocortical Layer V pyramidal neurons from individuals with drug-resistance epilepsy, particularly intratelencephalic-2 neurons, which exhibit regular firing, are not necessarily hyperexcitable at the somatic level. Instead, synaptic alterations, such as synaptic decoupling and the lack of frequency-dependent short-term depression, may significantly contribute to the hyperexcitable state observed during seizure activity.